PERSPEKTIF FILSAFAT HUKUM ISLAM ATAS HAK DAN KEWAJIBAN SUAMI ISTRI DALAM PERKAWINAN - Nasution, Muhammad Syukri Albani (Universitas Islam Negeri Raden Intan Lampung, 2015)
THE PERSPECTIVE OF THE ISLAMIC LAW PHILOSOPHY TOWARD THE RIGHTS AND OBLIGATION OF SPOUSE INMARRIAGE: The question appears: Can law in family describe the Fiqh by reviewing the interpretation of the texts of the Qur’an and hadith? The explanation in Lughawiyah, Istishlahiyah and Ta’liliyah is that the Islamic law is elastic which can constantly change by time, condition, and location. The Islamic law is not rigid. It comes to bring the live for human being. The law is not based on the book, fiqh, or other source by the lecturers or other people. In a relationship, rights and obligation of spouse has been illustrated clearly. Later, many people think that the interpretation is not satisfying. The previous time and recent time has been different and changing, different places, different cultures. Even it’s possible that the opinion of the previous interpretation is not always right.